Global responses to maritime violence cooperation and collective action - Shemella, Paul (Stanford University Press, 2016)
Global Responses to Maritime Violence is a full discussion of maritime security short of war that goes beyond the current literature in both scope and perspective. The chapters in this volume examine terrorism, piracy, armed robbery at sea, illegal maritime trafficking, illegal fishing, and other maritime crimes.